1998
DOI: 10.1007/s004140050165
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancing drugs (doping agents) and sudden death - a case report and review of the literature

Abstract: The case of sudden cardiac death of a 23-year-old body builder who used anabolic steroids combined with other performance enhancing drugs is reported. Postmortem investigations revealed cardiac hypertrophy, acute cellular necrosis and interstitial fibrosis of the myocardium. The side-effects and interactions of the substances used are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
9

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 44 publications
0
59
0
9
Order By: Relevance
“…A Swedish study suggested that AAS abuse is associated with an increased risk of premature death, especially among persons with additional substance abuse and/or psychiatric disease (Petersson et al 2006a). After long-term AAS abuse (sudden) cardiac death is the most common manifestation of AAS toxicity (Di Paolo et al 2007;Dickerman et al 1995;Fineschi et al 2007;Hausmann et al 1998;Luke et al 1990; own observation).…”
Section: Pathological Findingsmentioning
confidence: 97%
“…A Swedish study suggested that AAS abuse is associated with an increased risk of premature death, especially among persons with additional substance abuse and/or psychiatric disease (Petersson et al 2006a). After long-term AAS abuse (sudden) cardiac death is the most common manifestation of AAS toxicity (Di Paolo et al 2007;Dickerman et al 1995;Fineschi et al 2007;Hausmann et al 1998;Luke et al 1990; own observation).…”
Section: Pathological Findingsmentioning
confidence: 97%
“…Abuse of certain drugs, such as cocaine, as well as risk factors for IHD, such as obesity and diabetes, may trigger myocardial ischaemia and SCD. [67][68][69] Physical inactivity is also considered a major risk factor for IHD, whereas regular physical training reduces the risk of SCD during vigorous exertion. 70 The benefits of regular physical activity and sports participation are believed to outweigh the increased risk for coronary events triggered by acute, intensive exercise.…”
Section: Recommendationsmentioning
confidence: 99%
“…Nach einer amerikanischen Untersuchung sollen 7% der männlichen Oberschüler Steroide einnehmen -Tendenz steigend (DER SPIE- GEL 41, 1988). Die unübersehbaren Folgen des Dopingmissbrauchs vom Leberkarzinom bis zum plötzli-chen Herztod werden kaum beachtet [14,16,21,35,38]. Kritische Stimmen weisen darauf hin, dass der Dopingmissbrauch kein Problem der sportlichen Elite ist, sondern eine gesellschaftliche Dimension hat.…”
Section: Die Internistisch-kardiologische Betreuung Imunclassified